KAJIAN DAMPAK PARTISIPASI MASYARAKAT BANK SAMPAH MULYO SEDOYO GEREJA ISA ALMASIH JEMAAT PRINGGADING DI KELURAHAN BRUMBUNGAN KOTA SEMARANG TERHADAP EKSISTING BANK SAMPAH DI KOTA SEMARANG - Gunawan, Melissa Azelea (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2023)
This study aims to determine the existing condition of bank waste in Semarang City and the response of the surrounding community. This study uses a survey research method—data collection techniques using in-depth interviews, observation, angles, and documentation. The samples used in this study were several Mulyo Sedoyo waste bank customers with the criteria of having lived in Semarang for at least five years and being at least 17 years old. This sample will be the respondents who will answer the questionnaire from the researcher. The number of samples of 171 respondents was determined by the accidental sampling method. Our research results show that using social media and online platforms as product marketing is proven to be effective and increases turnover compared to conventional methods. The Garbage Bank in Mulyo Sedoyo has several obstacles that cause the Garbage Bank to run less effectively. The main problem is the need for more public interest in participating in the Garbage Bank and becoming a Garbage Bank customer. More active and active efforts are needed from the government to provide building assistance or movements to educate the importance of waste banks for the environment in general and the community's economy in particular.